The Limits of Evidence in Rhinoplasty - Gassner, Holger G.; Ordonez, Francisco; Nunes, Rita (Facial Plastic Surgery, 2023)
The broad trend toward minimally invasive methods in most surgical fields is contrasted by rhinoplasty: Extended open approaches, an increasing number of grafting techniques, donor site depletion, and extensive osteotomies seem to indicate a trend away from minimally invasive methodology for this particular procedure. This article intends to analyze which factors are involved in this and related developments in rhinoplasty.Evidence-based methodology sets the standards for scientific analysis. For rhinoplasty, however, limitations of established scientific methodology are identified. These include the relative lack of objective outcome measures and the impact of various systematic biases on reported results. These biases include operator dependence, interdependence of techniques, biased selection of outcome parameters, and orthodox treatment bias. Upon critical review, the importance of systematic biases may outweigh the impact of evidence-based study in rhinoplasty. Results should therefore be interpreted with caution. Strategies are suggested to identify and mitigate the impact of biases and to improve reporting and outcome analyses in rhinoplasty.
Keywords: evidence-based medicine; rhinoplasty; biases in rhinoplasty; quality of life